Alterations of the Ca2+ clearing mechanisms by type 2 diabetes in aortic smooth muscle cells of Zucker diabetic fatty rat - Moreno-Salgado, Adriana; Coyotl-Santiago, Nayeli; Moreno-Vazquez, Roberto; Lopez-Teyssier, Mayte; Garcia-Carrasco, Mario; Moccia, Francesco; Berra-Romani, Roberto (Frontiers in Physiology, 2023)
Type 2 Diabetes Mellitus (T2DM) is a rapidly rising disease with cardiovascular complications constituting the most common cause of death among diabetic patients. Chronic hyperglycemia can induce vascular dysfunction through damage of the components of the vascular wall, such as vascular smooth muscle cells (VSMCs), which regulate vascular tone and contribute to vascular repair and remodeling. These functions are dependent on intracellular Ca2+ changes. The mechanisms by which T2DM affects Ca2+ handling in VSMCs still remain poorly understood. Therefore, the objective of this study was to determine whether and how T2DM affects Ca2+ homeostasis in VSMCs. We evaluated intracellular Ca2+ signaling in VSMCs from Zucker Diabetic Fatty rats using Ca2+ imaging with fura-2/AM. Our results indicate that T2DM decreases Ca2+ release from the sarcoplasmic reticulum (SR) and increases the activity of store operated channels (SOCs). Moreover, we were able to identify an enhancement of the activity of the main Ca2+ extrusion mechanisms (SERCA, PMCA and NCX) during the early stage of the decay of the ATP-induced Ca2+ transient. In addition, we found an increase in Ca2+ entry through the reverse mode of NCX and a decrease in SERCA and PMCA activity during the late stage of the signal decay. These effects were appreciated as a shortening of ATP-induced Ca2+ transient during the early stage of the decay, as well as an increase in the amplitude of the following plateau. Enhanced cytosolic Ca2+ activity in VSMCs could contribute to vascular dysfunction associated with T2DM.